Numerical investigation on photovoltaic thermal panel using various nanofluids concentrations - Mohd Rosli, Mohd Afzanizam; Cheah, Kai Xiang; Probowo; Herawan, Safarudin Gazali; Teggar, Mohamed; Mitan, Nona Merry Merpati (Penerbit Akademia Baru, 2025)
Increasing the efficiency of solar panels is crucial for effective use of renewables. The present numerical study deals with improving the performance of a PVT system with nanofluid using CFD FLUENT software. ZnO-water and SiO2-water nanofluids are investigated and correlation are established between the PVT efficiency and various nanofluid volumetric concentrations ranging from 1% to 10%. Validation of the present results is verified by comparison with experimental data. Comprehensive research is conducted to evaluate the correlation between the thermophysical properties of nanofluids such as density, thermal conductivity, specific heat capacity and dynamic viscosity. The results demonstrate that the overall efficiency of the ZnO-water nanofluid and SiO2-water nanofluid increases by 0.44% and 0.24%, respectively, as the volumetric concentration of the nanofluid rises from 1% to 10%. The ZnO-water nanofluid reveals enhanced thermal and electrical efficiency compared to the SiO2- water nanofluid due to its superior thermal conductivity and enhanced heat transfer capabilities along the absorber tube. The ZnO-water nanofluid exhibits a greater heat transfer coefficient, thereby facilitating the cooling mechanism of the PV panel and reducing the PV cell temperature, hence enhancing power generation.